Analysis of Students’ Errors and Writing Flow: A Case Study in Written Process Paragraphs by the First Semester Students of English Department at the University of Mataram - Masyhadani, Rizki Putra; Thohir, Lalu; Saputra, Agus (Universitas Muhammadiyah Mataram, 2025)
This study analyzes students’ errors and writing flow in process paragraphs written by first-semester English Department students at the University of Mataram in the academic year 2024/2025. The objectives are to identify types of errors, evaluate the quality of writing flow, and perceive causes of errors. The data were obtained from 15 students’ process paragraphs and interviews with five students, then analyzed using Dulay et. al. (1982) Surface Strategy Taxonomy, Norrish’s (1983) causes of errors, and Oshima and Hogue’s (2006) framework for writing flow. The findings revealed a total of 60 errors consisting of misformation (40%), omission (30%), misordering (18.3%), and addition (11.7%). These errors were primarily caused by carelessness, translation habits, and first language interference, often occurring simultaneously. In terms of writing flow, all students successfully maintained a clear time sequence, 80% used appropriate transition signals, yet only 46.7% consistently applied the principle of one step per sentence. These weaknesses reduced sentence-level clarity despite overall chronological organization. In conclusion, the study shows that students’ challenges in writing process paragraphs are both grammatical and developmental, suggesting the need for grammar reinforcement alongside explicit instruction on coherence, transitions, and sentence clarity.